2013
DOI: 10.1073/pnas.1220835110
|View full text |Cite
|
Sign up to set email alerts
|

Frequent adaptation and the McDonald–Kreitman test

Abstract: Population genomic studies have shown that genetic draft and background selection can profoundly affect the genome-wide patterns of molecular variation. We performed forward simulations under realistic gene-structure and selection scenarios to investigate whether such linkage effects impinge on the ability of the McDonald-Kreitman (MK) test to infer the rate of positive selection (α) from polymorphism and divergence data. We find that in the presence of slightly deleterious mutations, MK estimates of α severel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
338
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(365 citation statements)
references
References 43 publications
(69 reference statements)
25
338
2
Order By: Relevance
“…Our results are broadly concordant with a recent examination of the ability of the McDonald-Kreitman (MK) test (McDonald and Kreitman 1991) to infer the fraction of substitutions that were adaptive (a) under a simulated recurrent hitchhiking scenario with constant population size (Messer and Petrov 2013). Their study found that Eyre-Walker and Keightley's distribution of fitness effects a (DFE-a) method (Eyre-Walker and Keightley 2009), which simultaneously estimates a, the DFE, and a two-epoch population size history, incorrectly inferred the presence of population size changes (Messer and Petrov 2013).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results are broadly concordant with a recent examination of the ability of the McDonald-Kreitman (MK) test (McDonald and Kreitman 1991) to infer the fraction of substitutions that were adaptive (a) under a simulated recurrent hitchhiking scenario with constant population size (Messer and Petrov 2013). Their study found that Eyre-Walker and Keightley's distribution of fitness effects a (DFE-a) method (Eyre-Walker and Keightley 2009), which simultaneously estimates a, the DFE, and a two-epoch population size history, incorrectly inferred the presence of population size changes (Messer and Petrov 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Positive selection may also affect estimation of multipopulation demographic scenarios: although we did not examine this here, Mathew and Jensen (2015) recently showed that selective sweeps will impair parameter estimates for a two-population isolationwith-migration model. Thus our results, combined with those of Mathew and Jenson (2015), Ewing and Jensen (2016), and Messer and Petrov (2013), strongly suggest that the problem of natural selection skewing demographic inference is a general one.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We infer that the population size of YRI and Drosophila expanded 2.3-fold 6,000 generations ago and 2.7-fold 500,000 generations ago, respectively (SI Appendix, Table S1). Note that demographic estimates from synonymous sites are biased by selection affecting linked neutral sites (13,14), but that this bias does not affect our ability to infer the DFE (14, 15) (SI Appendix, Text S3).…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing evidence that this is also true for many other organisms (1,3). Such processes have important implications for attempts to estimate demographic parameters, which usually ignore these complications, as has been pointed out before (53)(54)(55)(56). This is especially important when selection at linked sites distorts gene genealogies and hence site frequency spectra, because these are the main basis for inferring demographic parameters.…”
Section: Discussionmentioning
confidence: 95%